MENINGKATKAN HASIL BELAJAR PKn POKOK BAHASAN STRUKTUR ORGANISASI KABUPATEN/KOTA MELALUI METODE PEMBERIAN TUGAS PADA SISWA KELAS IV SDN SEBAMBAN BARU KABUPATEN TANAH BUMBU - Rauh Fikum (JURNAL SOCIUS, 2013)
The purpose of this study was to determine how the implementation of the method of giving the task of learning the organizational structure of the county / city. This study uses action research method. The results showed an increase in motivation and learning outcome of students understanding of civics material on Organizational Structure District Government/City with an average value of evaluation results is gradually increased, although not too signifikan.Pada first cycle of the first meeting with the average value of 5.80, At the second meeting with the average value increased slightly, namely 5.92. At the third meeting be 6,04.Sedangkan in Cycle II becomes 6.68, while the fourth meeting of KKM for subjects Civics Class IV SDN New Sebamban was 6.50 (corresponding SK Principal), and at the last meeting the average value of students into 7.28 or about 76 percent keberhasilan.Oleh because student learning outcomes have exceeded the indicator of the success of this study, the research was stopped at the fifth meeting as planned. This fact shows that learning outcomes Civics Government Organizational Structure of Matter Regency/City has reached as expected.Key words: students motivation and learning achievement